Analisa Kelayakan Bisnis Minuman Ringan Bestea - Vivi Vivi; Sonny Sonny (FIRM Journal of Management Studies, 2022)
Tea is a very common drinks especially in Indonesia. Since the global pandemic, many people changed their consumption habit and lifestyle to a healthier one and one of them is tea. Triggered by this event, the industry of tea drinks bloom. The business plan developed is named Bestea having meaning and similarity with the word bestie in which have a meaning of best friend. Bestea targeted their products to millenial and Z generation whose having a habit of hanging out with friends and family. Bestea  wants to widen the reach of market target by using apps such as GrabFood, GoFood, and ShoppeFood for things such as selling product and taking orders from customers online. The business of Bestea is targeted to reach and achieve revenue whereas each quartal months will give 5-15% of revenues for at least 5 years. Bestea expected to achieve payback period in the fourth year and will accumulate NPV at IDR 325.372.319, with return on assets on 35.77 percent and return on sales around 38 percent on the fifth years.Keywords : Tea business, feasibility study, business plan